Research method for composition design and anti-seepage performance of self-expanding grain composition
Through the design method of grading composition of self-expanding particles, the problems of long construction cycle, high difficulty and easy aging of materials in traditional leakage treatment methods are solved, and the efficient anti-seepage and ecologically friendly dual aspects of self-expanding particles in dam leakage management are achieved. Effect.
Patent Information
- Application Number
- CN202411266045.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-02-14
AI Technical Summary
The traditional leakage control method has a long construction cycle and is difficult, and anti-seepage materials are prone to aging and damage, and have a negative impact on the environment. It cannot effectively solve the hidden dangers of dam leakage and ecological protection problems.
The self-expanding particle grading composition design method is adopted to obtain the self-expanding particles of the required size through the screening device, calculate the pass rate of each particle size range according to the Taibo method, prepare the mixture of particles of different particle sizes, and conduct experimental verification and optimization until Obtain the optimal grading composition.
Self-expanding particles can quickly fill the leakage channel and form a tight anti-seepage layer. It has good anti-seepage effect, is simple to construct, has a long service life, is not easy to age and damage, is environmentally friendly, can effectively solve the hidden dangers of dam leakage and realize the ecological repair.
Smart Images

Figure CN119446348A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of anti-seepage performance of self-expanding particles, and in particular, relates to a self-expanding particle gradation composition design and an anti-seepage performance research method. Background Art
[0002] Seepage damage is the main factor causing the instability and destruction of water conservancy projects such as dams. It not only endangers infrastructure such as towns and major transportation arteries, but also seriously threatens the safety of life and property of the general public. If the hidden dangers of dam leakage are not discovered early and dealt with in a timely and effective manner, it may lead to catastrophic consequences. At present, traditional leakage control measures mainly include concrete anti-seepage, high-pressure grouting, splitting grouting and other methods. Although these methods can play an anti-seepage effect to a certain extent, they also have significant defects: first, these methods have a long construction period and often require a lot of time and manpower and material resources; second, the construction is difficult, especially under complex geological conditions, the construction process is more difficult; in addition, the anti-seepage materials used are prone to aging and damage, resulting in a gradual weakening of the anti-seepage effect, and these materials may have a negative impact on the surrounding environment and destroy the ecological balance. Therefore, traditional methods have significant deficiencies in anti-seepage control.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art, provide a method for researching the design of self-expanding particle grading composition and anti-seepage performance, and solve the problems raised in the above-mentioned background technology.
[0005] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:
[0006] A method for designing a self-expanding particle gradation composition comprises the following steps:
[0007] Step S1: obtaining self-expanding particles of a desired size through a sieving device, and calculating the self-expanding particles based on the Taybo method;
[0008] Step S2: according to the calculation results, preparing self-expanding particles of different particle sizes, and mixing them to obtain self-expanding particles of target gradation;
[0009] Step S3: experimentally verifying the self-expanding particles of the target gradation obtained in step S2, and testing the anti-seepage performance of the self-expanding particles of the designed gradation, until the self-expanding particle gradation of the preliminary gradation is obtained;
[0010] Step S4: Taking the preliminary gradation as the test object, an anti-seepage performance test is carried out according to the specification to determine the final gradation composition.
[0011] Through the above scheme: self-expanding particles can quickly fill the leakage channel and form a tight anti-seepage layer by absorbing water and expanding, which has a good anti-seepage effect. Compared with traditional materials, self-expanding particles are simpler in construction and can be directly constructed under underwater or wetland conditions, which greatly shortens the construction period and reduces the construction difficulty. At the same time, self-expanding particles have a long service life, are not easy to age and break, and can maintain good anti-seepage performance for a long time. More importantly, self-expanding particles are environmentally friendly and will not cause damage to the surrounding ecosystem, which helps to repair and protect the ecological environment. Therefore, the use of self-expanding particles for anti-seepage can not only effectively solve the hidden dangers of dam leakage, but also achieve the dual goals of ecological restoration.
[0012] Optionally, the self-expanding particles are formed by mixing bentonite, a quartz core and a polymer binder, wherein the inner core is quartz and the outer layer is a dry organic mineral coating layer.
[0013] Optionally, the steps for calculating the self-expanding particles based on the Talbot method are:
[0014] The passing rate of self-expanding particles in each particle size range is calculated according to the formula Px = 100*e*(d / D)n, where P x is the passing rate of self-expanding particles of a certain required particle size; e is the expansion reduction coefficient of the self-expanding particles, and the value range of the expansion reduction coefficient e is 0.3 to 0.6; d is the required particle size of a certain level of self-expanding particles; D is the maximum particle size of the self-expanding particles, and n is the reduction coefficient.
[0015] Optionally, the value range of d is 0.1 mm to 10 mm, and the value range of D is 1 mm to 100 mm.
[0016] Optionally, after obtaining the preliminary grading, nanomaterials are added to the optimal self-expanding particle grading, and the calculation formula is, P = (N / W) × 100%, wherein P is the weight percentage of the nanomaterial in the self-expanding particles, N is the weight of the nanomaterial, W is the total weight of the self-expanding particles, and the proportion of the nanomaterial is 0.1% to 5% of the total weight of the self-expanding particles.
[0017] Optionally, the nanomaterial includes but is not limited to one or a combination of two or more of nano silicon dioxide and nano aluminum oxide.
[0018] Optionally, after determining the preliminary grading, the particle morphology and surface roughness need to be adjusted, including the following steps:
[0019] The surface treatment of the self-expanding particles was performed by mechanical grinding and the formula Calculate the predetermined standard of surface roughness, and stop grinding after the surface roughness of the self-expanding particles reaches the predetermined standard, where Ra is the average surface roughness; n is the number of measurement points; Zi is the height of the i-th measuring point; Z m is the average height of all measurement points;
[0020] The treated self-expanding particles are remixed and tested for anti-seepage performance and based on the test results, the treatment method and conditions are further optimized until the particle morphology and surface roughness are optimal.
[0021] A research method for designing the composition of self-expanding particle gradation is provided, wherein the self-expanding particle gradation is tested using a test device, and the method comprises the following steps:
[0022] a: Clean the experimental area and level the earth and rocks of the embankment;
[0023] b: Spread the mixed self-expanding particles in the experimental area;
[0024] c: By controlling the water flow into the experimental area, the water inlet pressure is adjusted using a pressure-controlled water inlet system;
[0025] d: Use a measuring cylinder to collect water at the outlet pipe, record the seepage volume within 30 seconds, repeat the measurement 4 times until the seepage volume tends to be stable, analyze the measurement results and draw a graph of the relationship between the seepage volume and the seepage time;
[0026] e. According to the test results, the self-expanding particle gradation is optimized and adjusted, and steps a to d are repeated until the self-expanding particle gradation with the best anti-seepage performance is obtained.
[0027] Optionally, the test device includes a box, the interior of which is divided into a first space for placing self-expanding particles and a second space for storing soil and stone materials by a partition with mesh, one side of the first space is connected to a water inlet pipe, and one side of the second space is connected to a water outlet pipe.
[0028] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time:
[0029] 1. The self-expanding particles of the required size are accurately obtained through the sieving instrument, and the passing rate of each particle size range is calculated based on the Taybo method to ensure the scientificity and rationality of the particle distribution. Secondly, particles of different particle sizes are prepared and mixed to obtain the target gradation, which improves the uniformity and stability of the particles and ensures the uniformity and durability of the anti-seepage effect. Through experimental verification and repeated testing, the particle gradation is further optimized to ensure that the anti-seepage performance in actual application is optimal, reduce engineering risks, and improve the overall engineering quality and safety.
[0030] 2. By adding nanomaterials to the optimal self-expanding particle grading and calculating their weight percentage through precise formulas, the anti-seepage performance and self-repairing ability of the particles can be further enhanced, significantly improving the durability and adaptability of the material. The particle surface is mechanically ground and the predetermined standard of surface roughness is calculated through a formula to ensure the uniformity and appropriate roughness of the particle surface, improve the density and bonding force between particles, and further optimize the anti-seepage effect.
[0031] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The drawings described below are only some embodiments. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0033] In the figure:
[0034] Figure 1 Design process flow chart for self-expanding particle grading composition;
[0035] Figure 2 A three-dimensional schematic diagram of the test device.
[0036] In the accompanying drawings, the components represented by the reference numerals are listed as follows:
[0037] 1. Box body; 2. Partition; 3. First space; 4. Second space; 5. Water inlet pipe; 6. Water outlet pipe.
[0038] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION
[0039] The present invention will now be described in further detail with reference to the accompanying drawings.
[0040] See also Figure 1-2 As shown, in this embodiment, a self-expanding particle grading composition method is provided, comprising the following steps:
[0041] Step S1: Obtain self-expanding particles of the required size through a sieving instrument, and calculate the self-expanding particles based on the Taybo method, ensuring that the particle size distribution meets the design requirements, improving the uniformity and stability of the particles, and making the subsequent anti-seepage performance test more accurate and reliable. This method not only improves the repeatability and accuracy of the experiment, but also effectively reduces the error caused by uneven particle size, ensuring that the final designed self-expanding particle grading has excellent anti-seepage effect in practical applications, and improving the overall performance and safety of the material in engineering applications.
[0042] Step S2: According to the calculation results, self-expanding particles of different particle sizes are prepared and mixed to obtain self-expanding particles of target gradation. By accurately controlling the proportion of particles of each particle size, the particle gradation after mixing is ensured to be optimal, thereby significantly improving the overall performance and anti-seepage effect of the self-expanding particles. Through scientific preparation and mixing, the density and uniformity between particles can be ensured, the porosity between particles can be reduced, and the anti-seepage performance and structural stability of the material can be improved.
[0043] Step S3: Experimentally verify the self-expanding particles of the target gradation obtained in step S2, and test the anti-seepage performance of the self-expanding particles of the designed gradation until the self-expanding particle gradation of the preliminary gradation is obtained. The designed particle gradation is strictly tested and verified through actual experiments to ensure that it achieves the expected effect in terms of anti-seepage performance. Through repeated testing and adjustment, potential problems in particle gradation can be identified and optimized to ensure that the final selected preliminary gradation has the best anti-seepage ability and stability. This process not only improves the reliability and accuracy of the experiment, but also provides a scientific basis and technical guarantee for subsequent large-scale applications, ensuring the efficient application and long-term stability of self-expanding particles in actual engineering, thereby effectively reducing engineering risks and improving overall engineering quality and safety.
[0044] Step S4: Take the preliminary gradation as the test object, and conduct an anti-seepage performance test according to the specification to determine the final gradation composition. The preliminary gradation is systematically and scientifically verified through standardized test methods to ensure that its anti-seepage performance meets the high standards required for engineering applications. Testing according to the specification not only improves the reliability and comparability of the test results, but also ensures that the final gradation composition can maintain excellent performance under different working conditions.
[0045] In this embodiment, the self-expanding particles are formed by mixing bentonite, a quartz core and a polymer binder, wherein the inner core is quartz and the outer layer is a dry organic mineral coating layer.
[0046] In this embodiment, the steps of calculating the self-expanding particles based on the Taybo method are as follows:
[0047] The passing rate of self-expanding particles in each particle size range is calculated according to the formula Px = 100*e*(d / D)n, where P xis the passing rate of self-expanding particles of a certain required particle size; e is the expansion reduction coefficient of the self-expanding particles, and the expansion reduction coefficient e has a value range of 0.3 to 0.6; d is the required particle size of a certain level of self-expanding particles; D is the maximum particle size of the self-expanding particles, and n is the reduction coefficient. The value range of d is 0.1mm to 10mm, and the value range of D is 1mm to 100mm. Through the reasonable setting of each parameter in the formula, including the passing rate of self-expanding particles of a certain required particle size, the expansion reduction coefficient, the required particle size of a certain level of self-expanding particles, the maximum particle size and the reduction coefficient of the self-expanding particles, the particle size distribution of the self-expanding particles can be accurately controlled, so that it exhibits the best anti-seepage performance during use. The range of the expansion reduction coefficient is set between 0.3 and 0.6, which can reasonably reflect the expansion characteristics of the self-expanding particles in practical applications, ensure the practical feasibility of the calculation results, and effectively reduce the errors caused by uneven particle size, ensuring that the final designed self-expanding particle grading has excellent anti-seepage effect in practical applications.
[0048] In this embodiment, after obtaining the preliminary gradation, nanomaterials are added to the optimal self-expanding particle gradation, and the calculation formula is, P = (N / W) × 100%, where P is the weight percentage of nanomaterials in self-expanding particles, N is the weight of nanomaterials, W is the total weight of self-expanding particles, and the proportion of nanomaterials is 0.10%-0.555% of the total weight of self-expanding particles. The addition ratio of nanomaterials is accurately controlled by scientific calculation formulas to ensure their uniform distribution in self-expanding particles, thereby significantly improving the anti-seepage performance and self-repairing ability of the material. The addition of nanomaterials can not only fill the tiny pores between particles and further reduce the permeability, but also improve the structural stability and compressive strength of the material, so that it can show better performance in various complex environments. By strictly controlling the addition ratio of nanomaterials, it can be ensured that its performance advantages are maximized without significantly increasing costs, and the overall quality and durability of the project are improved.
[0049] This process also provides flexible adjustment space, optimizing the proportion of nanomaterials added according to specific engineering needs and environmental conditions, so that the self-expanding particles can achieve the best anti-seepage effect and economic benefits in practical applications. Ultimately, through the scientific addition and optimization of nanomaterials, the efficient implementation and long-term stable operation of engineering projects are ensured.
[0050] In this embodiment, the nanomaterial includes but is not limited to one of nano silicon dioxide and nano aluminum oxide, or a combination of two or more thereof.
[0051] In this embodiment, after determining the preliminary grading, it is also necessary to adjust the particle morphology and surface roughness, including the following steps:
[0052] The surface treatment of the self-expanding particles was performed by mechanical grinding and the formula Calculate the predetermined standard of surface roughness, and stop grinding after the surface roughness of the self-expanding particles reaches the predetermined standard, where Ra is the average surface roughness; n is the number of measurement points; Z i is the height of the i-th measuring point; Z m is the average height of all measurement points; by precisely controlling the roughness of the particle surface, the anti-seepage performance of the self-expanding particles can be significantly improved. Mechanical grinding can effectively remove the irregularities on the particle surface, making it more uniform, which is conducive to the close packing of particles, thereby reducing the porosity between particles. By calculating the predetermined standard of surface roughness, it is ensured that the particle surface treatment reaches the optimal state and avoids performance problems caused by over-grinding or under-grinding. The optimized particle morphology and surface roughness not only improve the density and stability of the particles, but also enhance the self-healing ability and durability of the material, further improving the overall quality and safety of the project.
[0053] The treated self-expanding particles are remixed and tested for seepage resistance. Based on the test results, the treatment methods and conditions are further optimized until the particle morphology and surface roughness are optimal. The benefit of this process is that repeated testing and optimization can ensure the best seepage resistance of the self-expanding particles in actual applications. Remixing the treated particles helps ensure their uniform distribution and improves the uniformity and consistency of the overall material. The seepage resistance test can provide direct performance feedback to help identify deficiencies in particle morphology and surface roughness. By gradually optimizing the treatment methods and conditions, the microstructure of the particles can be finely adjusted to ensure their density and stability, thereby significantly reducing the permeability and improving the overall seepage resistance of the material.
[0054] A research method for designing the composition of self-expanding particle gradation is provided, wherein the self-expanding particle gradation is tested using a test device, and the method comprises the following steps:
[0055] a: Clean the experimental area and level the earth and rocks of the embankment;
[0056] b: Spread the mixed self-expanding particles in the experimental area;
[0057] c: By controlling the water flow into the experimental area, the water inlet pressure is adjusted using a pressure-controlled water inlet system;
[0058] d: Use a measuring cylinder to collect water at the outlet pipe, record the seepage volume within 30 seconds, repeat the measurement 4 times until the seepage volume tends to be stable, analyze the measurement results and draw a graph of the relationship between the seepage volume and the seepage time;
[0059] e. According to the test results, the self-expanding particle grading is optimized and adjusted, and steps a to d are repeated until the self-expanding particle grading with the best anti-seepage performance is obtained. The consistency and accuracy of the experimental conditions are ensured by cleaning the experimental area and leveling the dam soil and stone materials. Secondly, the mixed self-expanding particles are evenly laid in the experimental area to ensure the uniformity of particle distribution. By controlling the water flow into the experimental area and using the pressure-controlled water inlet system to adjust the water inlet pressure, the actual working conditions can be simulated to provide accurate experimental data. Use a measuring cylinder to collect water at the outlet pipe and record the seepage volume within 30 seconds. Repeat the measurement many times to ensure the reliability and stability of the data. Analyzing the measurement results and drawing a relationship diagram between the seepage volume and the seepage time will help to intuitively understand the anti-seepage performance of the particles.
[0060] In this embodiment, the test device includes a box body 1, the interior of the box body 1 is divided into a first space 3 for placing self-expanding particles and a second space 4 for storing soil and stone materials by a partition plate 2 with a mesh, one side of the first space 3 is connected to a water inlet pipe 5, and one side of the second space 4 is connected to a water outlet pipe 6.
[0061] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.
Claims
1. A method for designing the gradation composition of self-expanding particles, characterized in that: The following steps are involved: Step S1: obtaining self-expanding particles of a desired size through a sieving device, and calculating the self-expanding particles based on the Taybo method; Step S2: according to the calculation results, preparing self-expanding particles of different particle sizes, and mixing them to obtain self-expanding particles of target gradation; Step S3: experimentally verifying the self-expanding particles of the target gradation obtained in step S2, and testing the anti-seepage performance of the self-expanding particles of the designed gradation, until the self-expanding particle gradation of the preliminary gradation is obtained; Step S4: Taking the preliminary gradation as the test object, an anti-seepage performance test is carried out according to the specification to determine the final gradation composition.
2. A method for designing the gradation composition of self-expanding particles according to claim 1, characterized in that: The self-expanding particles are formed by mixing bentonite, a quartz core and a polymer binder, wherein the inner core is quartz and the outer layer is a dry organic mineral wrapping layer.
3. A method for designing the gradation composition of self-expanding particles according to claim 1, characterized in that: The steps for calculating self-expanding particles based on the Talbot method are: The passing rate of self-expanding particles in each particle size range is calculated according to the formula Px = 100*e*(a / D)n, where P x is the passing rate of self-expanding particles of a certain required particle size; e is the expansion reduction coefficient of the self-expanding particles, and the value range of the expansion reduction coefficient e is 0.3 to 0.6; d is the required particle size of a certain level of self-expanding particles; D is the maximum particle size of the self-expanding particles, and n is the reduction coefficient.
4. A method for designing the gradation composition of self-expanding particles according to claim 3, characterized in that: The value range of d is 0.1mm to 10mm, and the value range of D is 1mm to 100mm.
5. A method for designing the gradation composition of self-expanding particles according to claim 1, characterized in that: After obtaining the preliminary grading, nanomaterials are added to the optimal self-expanding particle grading, and the calculation formula is, P = (N / W) × 100%, wherein P is the weight percentage of the nanomaterial in the self-expanding particles, N is the weight of the nanomaterial, W is the total weight of the self-expanding particles, and the proportion of the nanomaterial is 0.1% to 5% of the total weight of the self-expanding particles.
6. A method for designing the gradation composition of self-expanding particles according to claim 5, characterized in that: Nanomaterials include but are not limited to nano silicon dioxide, nano aluminum oxide, or a combination of two or more thereof.
7. A method for designing the gradation composition of self-expanding particles according to claim 1, characterized in that: After determining the preliminary grading, it is also necessary to adjust the particle morphology and surface roughness, including the following steps: The surface treatment of the self-expanding particles was performed by mechanical grinding and the formula Calculate the predetermined standard of surface roughness, and stop grinding after the surface roughness of the self-expanding particles reaches the predetermined standard, where Ra is the average surface roughness; n is the number of measurement points; Z i is the height of the i-th measurement point; Z m is the average height of all measurement points; The treated self-expanding particles are remixed and tested for anti-seepage performance and based on the test results, the treatment method and conditions are further optimized until the particle morphology and surface roughness are optimal.
8. A method for studying the anti-seepage performance of the self-expanding particle gradation composition design, using a test device to test the self-expanding particle gradation of claims 1-7, characterized in that: The following steps are involved: a: Clean the experimental area and level the earth and rocks of the embankment; b: Spread the mixed self-expanding particles in the experimental area; c: By controlling the water flow into the experimental area, the water inlet pressure is adjusted using a pressure-controlled water inlet system; d: Use a measuring cylinder to collect water at the outlet pipe, record the seepage volume within 30 seconds, repeat the measurement 4 times until the seepage volume tends to be stable, analyze the measurement results and draw a graph of the relationship between the seepage volume and the seepage time; e. According to the test results, the self-expanding particle gradation is optimized and adjusted, and steps a to d are repeated until the self-expanding particle gradation with the best anti-seepage performance is obtained.
9. The method for studying the anti-seepage performance of the self-expanding particle gradation composition design according to claim 8, characterized in that: The test device comprises a box (1), the interior of the box (1) being divided into a first space (3) for placing self-expanding particles and a second space (4) for storing soil and stone materials by a partition plate (2) with mesh holes, one side of the first space (3) being connected to a water inlet pipe (5), and one side of the second space (4) being connected to a water outlet pipe (6).